2014
DOI: 10.11622/smedj.2014103
|View full text |Cite
|
Sign up to set email alerts
|

Femoral head diameter in the Malaysian population

Abstract: CONCLUSIONMalaysians have a mean femoral head diameter of 44.9 ± 3.2 mm. Among our patients, Chinese patients had a significantly larger femoral head size than Malay and Indian patients. We also found that, in our cohort, men had significantly larger femoral head diameters than women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
(13 reference statements)
1
7
2
Order By: Relevance
“…This finding was consistent with that of a Malaysian study comprising the same racial groups. (6) During a hip hemiarthroplasty procedure, the femoral head is replaced with a shell that is of the exact size as the native femoral head (measured intraoperatively with a caliper). Thus, knowledge of the mean femoral head diameter size provides the surgeon with a guide to the optimal size of the shell that should be used to replace the femoral head.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was consistent with that of a Malaysian study comprising the same racial groups. (6) During a hip hemiarthroplasty procedure, the femoral head is replaced with a shell that is of the exact size as the native femoral head (measured intraoperatively with a caliper). Thus, knowledge of the mean femoral head diameter size provides the surgeon with a guide to the optimal size of the shell that should be used to replace the femoral head.…”
Section: Discussionmentioning
confidence: 99%
“…(4) Umer et al found that the proximal femur morphology of the general healthy population (age 20-50 years) in Pakistan differed significantly from those in Western countries. (5) Lee et al found that among the Chinese, Malay and Indian races in Malaysia, the Chinese had significantly larger femoral head sizes compared to the other races; (6) however, the authors did not study other parameters of the proximal femur besides the femoral head sizes. Chin et al described Asian women as having smaller distal femurs.…”
Section: Introductionmentioning
confidence: 99%
“…Found higher male values for the FNSA, although it was not statistically significant. Lee et al [19] found that Malaysian males have a significantly greater average FHD than females. Their study showed that the gender difference in the FHD is 4mm, which is clinically significant.…”
Section: Discussionmentioning
confidence: 98%
“…Similar observations were made by Lee et al, who found that men had a significantly larger mean femoral head diameter than women (47.7±2.8 mm versus 43.7±2.4 mm; p<0.05). 5 It should be noted that the morphometry of femur depends on the ethnicity of the patients as well. Lee and colleagues reported that the mean femoral head diameter was largest in Chinese patients (45.2±3.1 mm), followed by Indian (44.4±3.3 mm) and Malay (44.2±3.0 mm) patients.…”
Section: Discussionmentioning
confidence: 99%
“…4 Lee et al found that among the Chinese, Malay and Indian races in Malaysia, the Chinese had significantly larger femoral head diameters compared to the other ethnicities. 5 Chin et al found that Asian women have having smaller distal femurs as compared to males. 6 There is very limited data which informs about the variation in the femoral head diameters among Nepalese population.…”
Section: Introductionmentioning
confidence: 99%